Black grouse (Lyrurus tetrix) population status, reasons for decline and potential conservation measures from Western and Central Europe to Fennoscandia: a literature review - Hambálková, Lucie; Cukor, Jan; Brynychová, Kateřina; Ševčík, Richard; Vacek, Zdeněk; Vacek, Stanislav; Skoták, Vlastimil; Linda, Rostislav; Andersen, Oddgeir (Frontiers in Ecology and Evolution, 2024)
The long-term decline of the black grouse population throughout Europe is influenced by many factors that affect populations differently depending on the distribution range, from Central Europe to the Scandinavian countries. Therefore, we analyzed available literature sources to describe the main reasons for the population decline of this species and to suggest conservation measures. In total, 228 pieces of literature from 1955 to 2024 were analyzed for this study. Based on the literature analysis, it is clear that the drivers of population decline differ across the distributional range. In Central Europe, where the population is declining rapidly, habitat loss and forest fragmentation are crucial factors, as is the negative impact of tourism. In Scandinavia, where the population is gradually declining, decreasing breeding success and increasing chick mortality rates are generally considered the main negative factors. However, these factors also affect black grouse populations in Central Europe. It is crucial to acknowledge that a significant proportion of the contributing factors, such as predation and habitat loss, can be attributed to human activities. Therefore, it is necessary to emphasize that environmental protection should work hand in hand with wildlife managers to improve the situation.